Microwave dielectric characterization of binary mixture of diethylene glycol monomethyl ether with N, N-dimethylformamide - Patil1, P. W. Khirade1, *S. S. Dubal1, S. B. Sayyad2, S. S. (International Multidisciplinary Research Journal, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; margin-left: 34pt; border-left: medium none; margin-right: 34pt; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Dielectric relaxation measurements of Diethylene Glycol Monomethyl Ether (DGME) – N,N-dimethylformamide (DMF) binary mixtures have been carried out at 11 concentrations at four temperatures 288K to 318K, over the frequency range 10 MHz to 20 GHz using time domain reflectometry (TDR) technique. The mixtures exhibit a principle dispersion of the Davidson - Cole relaxation type at microwave frequencies. Bilinear calibration method is used to obtain complex permittivity spectra e*(w) from reflection coefficient spectra r*(w). A non linear least square fit method was used to obtain the static dielectric constant (es) and relaxation time (t). Excess permittivity (esE), Excess Inverse Relaxation time (1/t)E, Kirkwood correlation factor (geff and gf), Bruggeman factor (fB) and molar enthalpy of activation (DH)* are also calculated to study the solute – solvent interaction.